The Pavement Condition Index Functional Evaluation of Runway Pavement Used Pavement Condition Index (PCI) Method (Case Study : Fatmawati Soekarno Airport Provinsi Bengkulu) - Tody Amanah (Journal of Civil Engineering and Planning (JCEP), 2023)
Maintenance of air transportation infrastructure, in the pavement system section at Fatmawati Airport, Bengkulu Province and other airports in Indonesia, must had high performance, safety, security, reliability and sustainability. Routine inspection activities at major airports in Indonesia usually use the Pavement Condition Index (PCI) method as a parameter. This journal examines handling costs, handling periods and the minimum based on the reduction in PCI values due to existing traffic loads by building several types of handling scenarios. In addition, it also evaluates the structural performance of the runway pavement. The results of the PCI value analysis show that it is decreasing every year. This decline prediction used forecasting from previously obtained data. For 2016 the PCI value obtained was 89 (satisfactory), 2017 was 83 (satisfactory), and 2018 was 73 (sufficient). Based on the PCI value of 3 years and the growth in aircraft traffic, the impairment can be calculated by modeling the equation. The PCI prediction value in 2019 is 66 (fair), the PCI value in 2020 is 60 (fair), and the PCI value in 2021 is 54 (poor). It can be concluded that the increasing growth of aircraft traffic with routine maintenance will make the PCI value on the runway pavement decrease every year.